2023
DOI: 10.3390/bioengineering10060690
|View full text |Cite
|
Sign up to set email alerts
|

Automated Classification of Lung Cancer Subtypes Using Deep Learning and CT-Scan Based Radiomic Analysis

Abstract: Artificial intelligence and emerging data science techniques are being leveraged to interpret medical image scans. Traditional image analysis relies on visual interpretation by a trained radiologist, which is time-consuming and can, to some degree, be subjective. The development of reliable, automated diagnostic tools is a key goal of radiomics, a fast-growing research field which combines medical imaging with personalized medicine. Radiomic studies have demonstrated potential for accurate lung cancer diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Another bleak explanation could be that some studies did not apply the resampling correctly. If only cross-validation is used without an independent test set, it is of utmost importance that resampling is applied only to the training set and does not utilize the validation set in any way 20 , 21 . If this is not followed, a large bias can be expected 22 , 23 ; yet, this kind of error is common 24 and often cannot be detected without access to the code, which is most often not provided in radiomic studies.…”
Section: Discussionmentioning
confidence: 99%
“…Another bleak explanation could be that some studies did not apply the resampling correctly. If only cross-validation is used without an independent test set, it is of utmost importance that resampling is applied only to the training set and does not utilize the validation set in any way 20 , 21 . If this is not followed, a large bias can be expected 22 , 23 ; yet, this kind of error is common 24 and often cannot be detected without access to the code, which is most often not provided in radiomic studies.…”
Section: Discussionmentioning
confidence: 99%
“…Dunn et al. ( 29 ) emphasized the potential of artificial intelligence-based computer-aided diagnostic tools, integrating radiomics analysis image segmentation with supervised classification, to autonomously diagnose lung cancer subtypes. Shen et al.…”
Section: Progress In the Application Of Pet-related Radiomics In Lung...mentioning
confidence: 99%
“…Zhou (28) demonstrated that 18 F-FDG PET/CT radiomics features, in conjunction with machine learning techniques, can differentiate primary from metastatic lung lesions and identify lung cancer's histological subtypes. Dunn et al (29) emphasized the potential of artificial intelligence-based computeraided diagnostic tools, integrating radiomics analysis image segmentation with supervised classification, to autonomously diagnose lung cancer subtypes. Shen et al (30) effectively classified lung adenocarcinoma (ADC) and squamous cell carcinoma (SCC) by employing subregion-based radiomics features extracted from 18 F-fluorodeoxyglucose ( 18 F-FDG) PET/ CT images of 150 ADC and 100 SCC patients.…”
Section: Pet-related Radiomics Predicts Different Pathological Subtyp...mentioning
confidence: 99%
“…Radiomics is an emerging field of medicine that combines computer science, mathematics, and medical imaging to understand better and diagnose diseases ( 13 , 14 ). Radiomics analyzes large amounts of medical imaging data to extract useful information, helping doctors make more accurate diagnoses and treatment decisions ( 15 ).…”
Section: Introductionmentioning
confidence: 99%